Pengaturan hukum Tindakan Teknologi Pornografi Melalui Akses Media Internet - Amirudin Y. Dako (JURNAL LEGALITAS, 2009)
Pornography websites Existence phenomenon in internet always shows nonplusing improvement. The increasing of pornography sites caused by this business has promising business opportunity. Pornography phenomenon in internet world that is is not is controlled, can generate morale degradation which will take place continually, along with progress of technology that is becoming increases. Internet blooming makes governmental control to pornography matter is not maximally. In the end government feels difficulty to black out many pornography websites which every when emerging. To overcome pornography websites bloaming which more and more, it can be done by government not only relies on the law Products, especially criminal law, but also by increasing social values, culture, religion qnd morale effectively. Kata Kunci: Hukum, Teknologi, Pornografi, Media, Internet